Mating-type genes of the anamorphic fungus Ulocladium botrytis affect both asexual sporulation and sexual reproduction - Qun Wang (Nature Portfolio, 2017)
Abstract Ulocladium was thought to be a strictly asexual genus of filamentous fungi. However, Ulocladium strains were shown to possess both MAT1-1-1 and MAT1-2-1 genes as observed in homothallic filamentous Ascomycetes. Here, we demonstrate that the U. botrytis MAT genes play essential roles for controlling asexual traits (conidial size and number). Using reciprocal genetic transformation, we demonstrate that MAT genes from the related heterothallic species Cochliobolus heterostrophus can also influence U. botrytis colony growth, conidial number and size, and have a strong effect on the range of the number of septa/conidium. Moreover, U. botrytis MAT genes can also affect similar aspects of asexual reproduction when expressed in C. heterostrophus. Heterologous complementation using C. heterostrophus MAT genes shows that they have lost the ability to regulate sexual reproduction in U. botrytis, under the conditions we employed, while the reciprocal heterologous complementation demonstrates that U. botrytis MAT genes have the ability to partially induce sexual reproduction in C. heterostrophus. Thus, the genetic backgrounds of C. heterostrophus and U. botrytis play significant roles in determining the function of MAT genes on sexual reproduction in these two fungi species. These data further support the role of MAT genes in controlling asexual growth in filamentous Ascomycetes but also confirm that heterothallic and homothallic Dothideomycete fungi can be interconverted by the exchange of MAT genes.